SCHUMPETERIAN ‘GREAT GAP’ THESIS AND MEDIEVAL ISLAMIC ECONOMIC THOUGHT: INTERLINK BETWEEN GREEKS, MEDIEVAL ISLAMIC SCHOLARS AND EUROPEAN SCHOLASTICS - Ali Rama (Fakultas Syariah (Syari'ah Faculty ), 2017)
Abstract Joseph Schumpeter (1883-1950) in his magnum opus, History of Economic Analysis (1954) proposed a great gap thesis by saying that economic analysis begins only with the Greeks and was not reestablished until the rise of European Scholasticism in the hands of St Thomas Aquinas.In fact, this Schumpeterian great gap in economic thought coincides with the Islamic golden age, when various Muslim writers made substantial contributions in various fields of inquiry, including economic matters. A substantial body of contemporary economic is traceable to medieval Arab Scholastics such as Abu Yûsuf (731-798), Al Farabi (873-950), IbnuSina (980-1037), Al-Ghazalî (1058-1111), IbnuTaimiyah (1263-1328), and IbnuKhaldûm (1364-1442).There were interlinked between Greek intellectual legacy to Islamic medieval legacy and to Latin scholastic economics. The Arab scholarship itself stimulated by the Greeks and further developed in light of the Islamic Ethos, not only inspired Scholastic thought, but that much of that scholarship became incorporated in Scholastic writings.So this paper provides an academically objection to the Schumpeterian thesis by providing Islamic scholars’ contribution on economic thoughts. Additionally, the paper provides some issues on Islamization of contemporary economics. Key words: great gap, medieval Arab-Islamic scholastics, Islamization of Economics, Islamic worldview. Abstrak Joseph Schumpeter (1883-1950) dalam bukunya History of Economic Analysis (1954) memperkenalkan sebuah tesis ‘great gap’ dengan mengatakan bahwa analisis ekonomi hanya mulai dari Yunani dan tidak berkembang lagi sampai kemunculan ilmuan Skolastik Eropa di tangan St Thomas Aquinas. Namun kenyataannya, ‘great gap’ Schumpeter ini justru terjadi pada masak ejayaan Islam, yaitu ketigasejumlahsarjanadanilmuan Muslim memberikan kontribusi signifikan dalam berbagai jenis penemuan dan keilmuan termasuk dalam bidang ekonomi. Isi dari ilmu ekonomi kontemporer saat ini dapat dilacak kesamaannya dengan karya ilmuan Arab abad pertengahan seperti Abu Yûsuf (731-798), Al Farabi (873-950), Ibnu Sina (980-1037), Al-Ghazalî (1058-1111), Ibnu Taimiyah (1263-1328), dan Ibnu Khaldûm (1364-1442). Terdapat keterhubungan antara karya intelektual Yunani, ilmuan Muslim abad pertengahan dan Ilmuan skolastik. Ilmuan Arab sendiri ‘distimulasi’ oleh ilmuan Yunani yang selanjutnya dikembangkan sesuai dengan kerangka Islam dan banyak dari karya mereka memiliki kemiripan dengan tulisan Skolastik. Penelitian ini melakukan penolakan secara akademik atas tesis Shumpeter tentang ‘great gap’ dengan menunjukkan kontribusi ilmuan Muslim dalam pemikiran ekonomi. Penelitian ini juga membahas beberapa isu tentang Islamisasi ilmu ekonomi kontemporer.